2015
DOI: 10.2514/1.c032995
|View full text |Cite
|
Sign up to set email alerts
|

Gust Load Alleviation for a Regional Aircraft Through a Static Output Feedback

Abstract: The paper presents the design of a symmetric, active, gust load alleviation system for a regional transport aircraft, based on a static output feedback with a constrained structure. The design is carried out on a comprehensive finite state aeroservoelastic model, including sensor units and actuator transfer functions, and verified by taking into account saturated control positions, rates, and hinge moments. The controller is designed within a quadratic optimal framework, through a second-order Hessian-based op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The calculation results of an Airbus 300 aircraft indicated that the NID control logic works effectively in the aircraft trajectory control during the penetration of wind shear. Fonte, et al (199) designed a symmetric, active GLA system for a regional transport aircraft based on a static output feedback (SOF) with a constrained structure. The control surfaces of two ailerons and the elevator were taken into consideration.…”
Section: Analytical Investigationsmentioning
confidence: 99%
“…The calculation results of an Airbus 300 aircraft indicated that the NID control logic works effectively in the aircraft trajectory control during the penetration of wind shear. Fonte, et al (199) designed a symmetric, active GLA system for a regional transport aircraft based on a static output feedback (SOF) with a constrained structure. The control surfaces of two ailerons and the elevator were taken into consideration.…”
Section: Analytical Investigationsmentioning
confidence: 99%
“…However, this does not adversely a↵ect our main conclusions because our approach leads to similar structural component thickness distributions to those obtained from studies that include more load conditions [11,12]. Furthermore, active maneuver and gust load alleviation systems could potentially reduce the need to include many critical structural load cases [13]. It is important to note that our objective in the present work is to study the main trends, not to perform detailed wing design.…”
Section: Nasa Had Experimentally Investigated the Drooped Wing Concepmentioning
confidence: 79%
“…However, the dependence of the unsteady aerodynamic forces on the second time derivative resulting from the classical RFA fit [4] for compressible flow may be seen as a low frequency residualization of its high frequency behaviour [41]. In this work, a residualization of the aerodynamic forces is also done in the limit of s → ∞ when considering compressible flow, see Section 3.1.…”
Section: Application To Unsteady Incompressible Flowmentioning
confidence: 99%